Effect of Soaking Time and Sb2O3 Concentration on Number of Bubble and Optical Properties of Borosilicate Glasses. Issue 1 (29th December 2021) - Singkiburin, N.; Srisittipokakun, N.; Sangsawat, Y.; Boonpa, W.; Kim, H. J.; Prasatkhetragarn, A.; Rajagukguk, J.; Thowladda, W.; Kaewkhao, J.
Abstract: Borosilicate glasses were fabricated with antimony oxide (Sb2 O3 )-doped in the formula of SiO2 -B2 O3 -Na2 O-CaO-ZnO, by using the melt-quenching method at 1200 °C which various soaking time of 3, 4, 5, 6, and 7 h. The results show that the density, molar volume and refractive index of glasses increased with increasing of Sb2 O3 concentration. However, the density of glasses decreases with increasing soaking time. The transmittance spectra present the absorption around 1050 nm and 450 nm which corresponds to Fe 2+ ion and Fe 3+ ion, respectively. This absorption strength decreases with increasing Sb2 O3 concentration which shows the highest strength at 0.0 mol% of Sb2 O3 content. Moreover, the decrease in the number of bubbles in the glass is dependent on the increase of the Sb2 O3 concentration and soaking time.